Similarity of 26 New Released Rice Varieties and Rice Parental Hybrids Based on 36 SSR Markers - Susanto, Untung; Satoto, Satoto; Rohmah, Nofi A.; Mejaya, Made Jana (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
More than 200 rice varieties had been released in Indonesia, but the genetic variability among those released varieties was suspected to be relatively low. Molecular markers, especially SSR could be used as a tool to disect the distinctness among rice genotypes, albeit phenotipically similar varieties. The technique could also be used to prove the authenticity of a variety. This research was aimed to obtain DNA fingerprinting data of new released rice varieties and hybrid parental lines using SSR markers. A total of 26 rice genotypes consisted of three upland, ten irrigated, five swampy rice varieties, along with eight hybrid parental lines were used in this experiments. The DNA was extracted from young leaf samples using CTAB modified method and was amplified with 36 SSR markers linked to important rice traits which spread accross the 12 rice chromosomes. The experiment was conducted in Plant Breeding Laboratory of Indonesian Center for Rice Research (ICRR) during 2012. The results showed that PIC value of the genotypes were mostly at medium level of the genetic diversity with the average value of 0.4451. The phylogenetic analysis showed that at the genetic distance of 10%, the genotypes were separated into 9 groups, i.e. Inpago 6, Inpara 5, and BH33d each stood alone while (Inpara 1, Inpara 2 , and Inpara 3); (Inpari 18 and Inpari 19, Inpago 4, Inpago 5, and Inpara 4); (Inpari 11, Inpari 12, Inpari 13, Inpari 14, Inpari 15, Inpari 16, Inpari 17, and Inpari 20); (GMJ6B, B6, and IR79156B); (PK21, BH95E, Bio9, and R14) each belong to one group. The grouping of the genotypes in this study seemed to follow the adaptation type to agro ecosystems. The hybrid parental lines tended to stay in different group from the inbred varieties. The application of these 36 SSR markers was able to distinguish among 26 genotypes rather distinctly.The use of more markers should give more powerful data to distinguish among genotypes.